Secreted Factors From Intervertebral Disc Cells and Infiltrating Macrophages Promote Degenerated Intervertebral Disc Catabolism. Issue 9 (1st May 2019) - Yang, Hao; Liu, Bo; Liu, Yajun; He, Da; Xing, Yonggang; An, Yan; Tian, Wei
Abstract : Study Design: Rat nucleus pulposus (NP) cells or annulus fibrosus (AF) cells were stimulated with conditioned media of RAW 264.7 macrophages and vice versa under healthy culture conditions and in the presence of pro-inflammatory mediators. The gene expression of pro-inflammatory mediators, extracellular matrix (ECM)-modifying enzymes, and chemokines, which play important roles in intervertebral disc degeneration (IDD), was determined. Objective: To test whether the interaction between native disc cells and infiltrating macrophages accelerates inflammation state, disrupts matrix homeostasis, and promotes inflammatory cells infiltration. Summary of Background Data: With macrophages infiltration, the disc resident cells would be inevitably exposed to macrophages. Macrophages have been shown to play pro-inflammatory role in the cellular interactions with disc cells under healthy culture conditions. However, the biologic interactions between macrophages and disc cells under degenerated disc inflammatory environment remain unknown. Methods: Murine Macrophages RAW 264.7 were cultured in the conditioned media of Rat AF or NP cells culture in the presence or absence of IL-1β stimulation. Similarly, Rat AF or NP cells were also cultured in the conditioned media of Murine Macrophages RAW 264.7 culture in the presence or absence of IFN-γ stimulation. The mRNA levels difference of pro-inflammatory genes, catabolic genes and chemokines genes for AF cells, NP cells and Macrophages RAW 264.7 were analyzed by qRT-PCR, respectively. Results: Compared with serum-free media exposure, RAW 264.7 macrophages exposed to AF or NP cells conditioned media selectively modestly upregulated mRNA levels of the aforementioned cytokines. Exposure of RAW 264.7 macrophages to conditioned media from AF or NP cells with IL-1β stimulation dramatically increased mRNA levels of all the investigated cytokines. Similarly, compared with serum-free media exposure, AF or NP cells exposed to RAW 264.7 macrophages conditioned media selectively modestly upregulated mRNA levels of the aforementioned cytokines. Exposure of AF or NP cells to conditioned media from RAW 264.7 macrophages with IFN-γ stimulation dramatically increased mRNA levels of all the investigated cytokines. Conclusion: The biologic interactions between infiltrating macrophages and native disc cells under degenerated disc inflammatory environment lead to an increasingly severe inflammatory conditions, which may be a self-stimulated process from the macrophages infiltration occurrence Level of Evidence: 5 Abstract : Exposure of macrophages to conditioned media from AF or NP cells with IL-1β stimulation dramatically up-regulated catabolic cytokines. Similarly, exposure of AF or NP cells to conditioned media from macrophages with IFN-γ stimulation dramatically up-regulated catabolic cytokines.